PEMBINAAN KELUARGA SAKINAH PERSPEKTIF DAKWAH FARDHIYAH DI KELURAHAN BORONG KOTA MAKASSAR - Abbas, Besse Hadijah (Jurnal Dakwah Tabligh, 2019)
This paper discusses the Sakinah family coaching with a perspective of Da’wah Fardhiyah in Borong Village of Manggala District of Macassart City. This paper investigates the issue by addressing it elaborates the Da’wah Fardhiyah methods for Sakinah family coaching. The factors are related to economy and aqida (faith). The aims of this issue is “How the method of Sakinah family coaching with a perspective of Da’wah Dardhiyah in Borong Village of Manggala District of Macassart City. In investigating the issue, this paper employ field research design by using personal communication approach and interpersonal da’wah approach. Furthermore, the samples for this research were selected using purposive sampling technique. This research collect primary and secondary data using interviews, observations and documentations. It processes the research data qualitatively through data reduction and conclusion. The data validity is achieved through four data triangulation methods, namely method triangulation, triangulation between researchers, data source triangulation and theory triangulation. Conclusion of Sakinah family is an ideal concept of a happy family. This research implies that Sakinah family can be achieved by maintaining strong will as well as good relationships with Allah, family members and show mutual love, undertanding, respect and helpfulness and good community members.